Platelet-derived growth factor-BB attenuates titanium-particle-induced osteolysis in vivo. (1st November 2016) - Ye, Chenyi; Zhang, Wei; Jiang, Shuai; Yu, Yuanbin; Zhou, Xiaoyu; Zhu, Ling; Xue, Deting; He, Rongxin
Abstract: Inflammation and osteoclastogenesis play critical roles in wear-particle-induced periprosthetic osteolysis (WPO). Platelet-derived growth factor-BB (PDGF-BB) could promote osteogenesis and inhibit inflammatory response. The aim of this study was to investigate the impact of PDGF-BB on WPO. Mice were divided into four groups, namely, sham, vehicle, low-, and high-dose PDGF-BB groups. Mice in the rhPDGF-BB groups were treated with PDGF-BB at 0.25 or 1 mg/ml/kg/day. Mice in the sham and vehicle groups received PBS daily. Two weeks after surgery, calvariae were harvested. Immunohistochemical analysis and μ-CT showed that PDGF-BB significantly reduced osteoclast formation and bone resorption. ELISA showed that rhPDGF-BB decreased the secretion of TNF-α, IL-1β, and IL-6. Western blotting revealed that rhPDGF-BB stimulated the expression of osteocalcin and osteoprotegerin. Furthermore, more VEGF and CD31 proteins were observed due to PDGF-BB by immunofluorescence. In conclusion, these findings suggest that rhPDGF-BB represents a potential treatment for WPO.